2014
DOI: 10.1016/j.compfluid.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive modeling study of in-cylinder fluid flows in a high-swirl, light-duty optical diesel engine

Abstract: The effectiveness of computational fluid dynamics modeling as a tool for researching fuel-lean, low temperature engine combustion strategies relies on its capability to capture the local fluid flow properties that affect spray dynamics, mixture preparation and ignition kinetics. In this study, a comprehensive model of an optically accessible, single-cylinder light-duty diesel engine was developed for engine combustion research. The computational model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…Perini et al [68] exhibited an optically accessible light duty single cylinder comprehensive model for an engine combustion research. Their computational model includes the realistic combustion chamber and ducts geometries.…”
Section: Effect Of Swirl Ratiomentioning
confidence: 99%
“…Perini et al [68] exhibited an optically accessible light duty single cylinder comprehensive model for an engine combustion research. Their computational model includes the realistic combustion chamber and ducts geometries.…”
Section: Effect Of Swirl Ratiomentioning
confidence: 99%
“…for engine combustion research. The results showed that Reynolds averaged Navier Stokes turbulence modeling approach is suitable for computational modeling of cycle averaged experimental measurements . As stated above, the CFD models are often not predictive of engine exhaust emissions due to the use of reduced chemical kinetic mechanisms.…”
Section: Introductionmentioning
confidence: 95%
“…The sector mesh lacks some geometric details such as valve cut-outs on the piston surface and valve recesses on the cylinder head that lead to a different geometry of the bowl rim and squish regions, and change the global flow properties also due to the 600 need of calibrating an 'effective' squish height to capture the global compression ratio correctly. Also, it was previously demonstrated that a sector mesh model is not able to capture proper turbulence quantities which define the rate of local fuel-air mixing (Perini et al (2014)).…”
Section: Mixture Preparation In a Light-duty Optical Diesel Enginementioning
confidence: 99%